Power analysis-resistant based on NCL path balance - Fang LUO; Qing-yu OU; Xiao-ping WU (Tongxin xuebao)
Because of the insufficient research on the essence and the design technique of the path balance structure, the experience of the designer is severely relied on, so it can't be applied in kinds of automatization synthesis techniques. To solve this problem, the formal specification and the sufficient conditions of the implementation for the path balance structure were researched, and the proof was given. Based on the improvement of the binary decision diagram, a path balance extension technique of the null convention logic (NCL) asynchronous circuit was put forward, which could be applied in kinds of automatization synthesis techniques. By applying this technique, the path balance structure of the NCL asynchronous circuit could be implemented on the premise that the characteristics of the orientated circuit would be un-changeable, and the leakage of the side-channel information aroused by the differences of the parasitic capacitor and the load capacitor could also be resisted.